James and the giant peach : a play - George, Richard R.; Dahl, Roald (New York, N.Y. : Puffin Books, 2007)
This dramatization of Roald Dahl's beloved book can be performed in school and at summer camp, acted out at home or simply read together by a group of friends.
At head of title: Roald Dahl's.
"First published in Great Britain by Puffin Books, 1982"--T.p. verso.
Keywords: Children's plays, English; Drama